Lesson Study as a Catalyst for Innovation in Ecuadorian English Classrooms: Teacher Experiences and Challenges - Egüez Carrión, Sofía (2025)
This study explores the implementation of Lesson Study (LS) as an innovative approach within the Ecua dorian educational context, where innovation is an emerging concept. With limited prior exposure to collaborative methodologies, many Ecuadorian teachers have yet to engage in practices that promote shared learning and professional growth. The researchers aim to investigate how LS, as a collaborative model, can foster innovation among educators by enhancing teamwork, shared responsibility, and a cooperative culture. Using a qualitative methodology rooted in narra tive inquiry, two volunteer English teachers who participated in an LS workshop were interviewed in depth to capture their reflections and perceptions of LS as an innovative tool. The collected data were analyzed through content analysis, allowing themes and categories to emerge around the teachers' understanding of innovation and the role of technology in education. Key findings indicate that while technology is commonly viewed as a potential driver of innovation, the teachers also recognize that innovation can be achieved through new teaching approaches aside from technology. LS was perceived as a beneficial collaborative method that strengthens professional relationships and introduces sustainable change in teaching practices. In conclusion, the study suggests that LS has significant potential as an innovative asset for Ecuadorian educators, offering a non-technological pathway to improve teaching and learning practices and encourage a shift toward a more collaborative educational culture.